Friction stir welding of 3D printed melt flow compatible dissimilar thermoplastic composites. (May 2021) - Kumar, Ranvijay; Singh, Rupinder; Ahuja, IPS
This study deals with the friction stir welding of 3D printed thermoplastic composites. In this study, the electrolytic Al metal particulate reinforced with the acrylonitrile butadiene styrene (ABS) and polyamide 6 (PA6) with 15% and 50% weight proportion respectively confirmed the feasibility of joining. Investigations have been made on welded joints prepared with consumable friction stir welding tool on 3D printed functional prototypes of ABS-15Al and PA6-50Al thermoplastic composites (for optimizing mechanical, morphological, and thermal properties). The online monitoring of temperature and friction stir welding (through thermal imaging camera) and axial force measurement (based upon milling dynamometer) has been made to understand the mechanism/changes in the mechanical, morphological, and thermal properties. Overall, best mechanical properties were observed at 1400 r/min, 50 mm/min feed rate, and 4 mm consumable plunge depth.